Sentidos primitivos de la demostración en la formación de profesores - Sanjuán, Arturo; Romero, Jaime; Bonilla, Martha (Revista Científica, 2012)
The first emerging meanings of the proof process, given by a group of five prospective teachers is studied in the context of real numeric continuum. The metodology is a teaching experiment of a six month long. The data analysis is made with de vignettes method. The conclusion is that there are three primitive meanings of the mathematical proof process. One of them imitates manners of the formal proof and this is what proposed as the paraformal proof.